Letter to the Editor: Spatial proximity of tumor–immune interactions predicts patient outcome in hepatocellular carcinoma - Gaoyao Peng; Jiangfa Li; Xinchou Wang (Discover Oncology)
Abstract We read with interest the study entitled "Spatial proximity of tumor-immune interactions predicts patient outcome in hepatocellular "in Hepatology (Maestri E, Kedei N, Khatib S, et al. in Hepatology 79(4):768–79, 2024). This study utilized highly multiplexed CODEX imaging to comprehensively analyze the spatial interactions between tumor and immune cells in hepatocellular carcinoma (HCC), yielding several meaningful findings and innovatively proposing the concept of the spatial neighborhood of immune cell infiltration and confirming its association with patient prognosis. After reading the article carefully, we have some suggestions to point out.